(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
The article studied the properties of complexation of radionuclides with humic acids in soil. It has been established that humic acids can form complex compounds with radionuclides of cesium-137, strontium-90 and potassium-40 in the soil.